Exploration of Ethnoscience in Sidoarjo Batik as a Local Wisdom-Based Learning Resource for Elementary School Students - Fitriyah, Nur; Widodo, Wahono; Gunansyah, Ganes (Journal of Innovation and Research in Primary Education, 2025)
This research explores the integration of ethnoscience within the traditional batik-making process in Sidoarjo as a contextual learning resource for elementary school students. The study aims to identify scientific concepts embedded in local cultural practices and analyze their relevance to the IPAS (Integrated Science and Social Studies) curriculum. Using a qualitative ethnographic method, data were collected through participatory observation, in-depth interviews, and documentation at Batik Tulis Al-Huda in Sidoarjo. Findings reveal that each stage of the batik process—from molani (sketching motifs), malemi (applying wax), nyolet (coloring), to nglorod (wax removal)—reflects basic scientific principles such as heat transfer, changes in states of matter, diffusion, and evaporation. These concepts align with key IPAS learning objectives at the elementary level. The study highlights how incorporating local wisdom into science education can foster scientific literacy, cultural identity, and contextual understanding among students. The research contributes to the development of culturally responsive teaching strategies and supports the Merdeka Belajar (Freedom to Learn) curriculum by linking classroom content to students’ cultural environment. It is recommended that future studies expand to other regions and examine how ethnoscience-based resources impact student learning outcomes. This study includes 25 references, 7 observation photos, and qualitative analysis tables to support the findings.